PERANCANGAN SISTEM INFORMASI PENJUALAN RUMAH BERBASIS WEB PADA PT.AGUNG SELARAS GROUP PEKANBARU - Rahmaddion, Armiza; Arrribe, Edo (JURNAL ILMIAH INFORMATIKA, 2024)
In the current digital era, a housing sales information system is a crucial component in the operations of property companies. The use of web-based information technology has become a necessity to enhance efficiency and expand market reach. Therefore, this research aims to design and develop a web-based housing sales information system for PT. Agung Selaras Group Pekanbaru. The research methodology includes analysis, system design, implementation, and testing phases. The result of this research is a web-based housing sales information system that can assist PT. Agung Selaras Group Pekanbaru in efficiently managing the housing sales process. This system is equipped with features such as detailed housing information, housing search based on specific criteria, booking processes, and online payments. Additionally, the system allows users to view housing photo galleries, obtain contact information, and provide reviews for the purchased houses.